Realised added value in dynamical downscaling of Australian climate change - Di Virgilio, Giovanni; Evans, Jason P.; Di Luca, Alejandro; Grose, Michael R.; Round, Vanessa; Thatcher, Marcus (Climate Dynamics, 2020)

Projected changes in vertical temperature profiles for Australasia - Ji, Fei; Evans, Jason P.; Di Virgilio, Giovanni; Nishant, Nidhi; Di Luca, Alejandro; Herold, Nicholas; Downes, Stephanie M.; Tam, Eugene; Beyer, Kathleen (Climate Dynamics, 2020)

Rapid Warming in the Australian Alps from Observation and NARCliM Simulations - Ji, Fei; Nishant, Nidhi; Evans, Jason P.; Di Luca, Alejandro; Di Virgilio, Giovanni; Cheung, Kevin K. W.; Tam, Eugene; Beyer, Kathleen; Riley, Matthew L. (Atmosphere, 2022)
The Australian Alps are the highest mountain range in Australia, which are important for biodiversity, energy generation and winter tourism. Significant increases in temperature in the past decades has had a huge impact on biodiversity and ecosystem in this region. In this study, observed temperature is used to assess how temperature changed over the Australian Alps and surrounding areas. We also use outputs from two generations of NARCliM (NSW and Australian Regional Climate Modelling) to investigate spatial and temporal variation of future changes in temperature and its extremes. The results show temperature increases faster for the Australian Alps than the surrounding areas, with clear spatial and temporal variation. The changes in temperature and its extremes are found to be strongly correlated with changes in albedo, which suggests faster warming in cool season might be dominated by decrease in albedo resulting from future changes in natural snowfall and snowpack. The warming induced reduction in future snow cover in the Australian Alps will have a significant impact on this region.

Global hotspots for the occurrence of compound events - Ridder, Nina N.; Pitman, Andy J.; Westra, Seth; Ukkola, Anna; Do, Hong X.; Bador, Margot; Hirsch, Annette L.; Evans, Jason P.; Di Luca, Alejandro; Zscheischler, Jakob (Nature Communications, 2020)
Abstract Compound events (CEs) are weather and climate events that result from multiple hazards or drivers with the potential to cause severe socio-economic impacts. Compared with isolated hazards, the multiple hazards/drivers associated with CEs can lead to higher economic losses and death tolls. Here, we provide the first analysis of multiple multivariate CEs potentially causing high-impact floods, droughts, and fires. Using observations and reanalysis data during 1980–2014, we analyse 27 hazard pairs and provide the first spatial estimates of their occurrences on the global scale. We identify hotspots of multivariate CEs including many socio-economically important regions such as North America, Russia and western Europe. We analyse the relative importance of different multivariate CEs in six continental regions to highlight CEs posing the highest risk. Our results provide initial guidance to assess the regional risk of CE events and an observationally-based dataset to aid evaluation of climate models for simulating multivariate CEs.